2018
DOI: 10.1155/2018/1624573
|View full text |Cite
|
Sign up to set email alerts
|

Promising Biosurfactant Produced by Cunninghamella echinulata UCP 1299 Using Renewable Resources and Its Application in Cotton Fabric Cleaning Process

Abstract: A biosurfactant was produced from Cunninghamella echinulata using sustainable technology for cleaning and degreasing of cotton fabric impregnated with burned motor oil. The surface tension was 32.4 mN/m on a medium containing instant noodle waste (2%), corn steep liquor (2%), and postfrying oil (0.5%) with a carbon/nitrogen ratio of 30 : 1, yield of 6.0 g·L−1, emulsifier index of 81.4%, and dispersant property of 32.15 cm2. The biosurfactant produced is a glycolipid constituted by carbohydrate (47.7%) and lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 50 publications
0
19
0
2
Order By: Relevance
“…Glucose, peptone, ZnCl 2 , MgSO 4 , and Tween 80 chemicals were purchased from Merck (Darmstadt, Germany). e chemical composition of WSO used in this study was reported by Andrade et al [21].…”
Section: 2mentioning
confidence: 99%
“…Glucose, peptone, ZnCl 2 , MgSO 4 , and Tween 80 chemicals were purchased from Merck (Darmstadt, Germany). e chemical composition of WSO used in this study was reported by Andrade et al [21].…”
Section: 2mentioning
confidence: 99%
“…(Santos et al, 2019), among others (Table 1). Regarding yeast strains, Candida species, particularly Candida tropicalis (Almeida et al, 2017;Batista et al, 2010;Junior et al, 2018;Rubio-Ribeaux et al, 2017), are the most studied for biosurfactants production from WCO, but other species (Andrade et al, 2018;Camargo et al, 2018;Niu et al, 2019) were studied (Table 2). Unlike to bacteria cultures, in biosurfactants production by yeast, normally WCO are used as co-substrate or inductor and not as the only carbon source (Almeida et al, 2017;Campos et al, 2014;Junior et al, 2018;Kanna, 2018;Pinto et al, 2018;Rubio-Ribeaux et al, 2017).…”
Section: Biosurfactantsmentioning
confidence: 99%
“…Most of the biosurfactants produced and commercialized are produced mainly by bacteria and yeasts, but recent studies have highlighted the production of these compounds by filamentous fungi (CHAVES, 2017;. In this sense, Mucoralean fungi have been investigated due to their potential to produce biosurfactants, as demonstrated by ANDRADE et al (2018), SILVA et al (2014), BIONE et al (2016), PELE et al (2018 and MARQUES et al (2019). However, this is the first report on the production of biosurfactant by representatives of the genus Absidia.…”
Section: Biomass (G/l)mentioning
confidence: 99%
“…Biosurfactants are amphipathic molecules with ability to display a variety of surface activities that, among other roles, help solubilizing hydrophobic substrates and are the subject of intense investigation (ANDRADE et al, 2018;FERREIRA et al, 2020). One of the major potential applications is their use as replacements for synthetic surfactants in many existing and future industrial and environmental applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation